2023
DOI: 10.1017/jfm.2023.707
|View full text |Cite
|
Sign up to set email alerts
|

Scaling law of structure function of Richtmyer–Meshkov turbulence

Zhangbo Zhou,
Juchun Ding,
Wan Cheng
et al.

Abstract: The scaling law of the structure function of Richtmyer–Meshkov (RM) turbulence is investigated both numerically and theoretically. High-fidelity simulations with a minimum-dispersion, adaptive-dissipation scheme are first performed. Results show that the mixing width experiences an exponential growth and the turbulent kinetic energy has a visible $-3/2$ spectrum. The scalar field exhibits a greater degree of intermittency than the velocity field, and also the small-scale statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(164 reference statements)
1
4
0
Order By: Relevance
“…2010), Note the evolutions of the mixing width for cases 1 and 3 have been reported in our previous work (Zhou et al. 2023 a ). Here, it is found that the mixing width in case 2 is nearly identical to that of case 1.…”
Section: Characteristics Of the Mixing Layersupporting
confidence: 59%
See 3 more Smart Citations
“…2010), Note the evolutions of the mixing width for cases 1 and 3 have been reported in our previous work (Zhou et al. 2023 a ). Here, it is found that the mixing width in case 2 is nearly identical to that of case 1.…”
Section: Characteristics Of the Mixing Layersupporting
confidence: 59%
“…In addition, the growth rate of the mixing width, , has a fitted value of 0.220 in case 2 that is nearly identical to 0.211 in case 1, whereas the fitted value of in case 3 is notably higher () (Zhou et al. 2023 a ). The value of in the broadband case is lower than the model prediction value (Youngs 2004; Soulard et al.…”
Section: Characteristics Of the Mixing Layermentioning
confidence: 99%
See 2 more Smart Citations
“…Anomalous scalings of active scalars in homogeneous turbulence were developed by Ching & Cheng (2008). Kinetic and scalar structure function scaling laws for RMI turbulence have been investigated through simulations and theory by Zhou et al (2023). The Batchelor spectrum of passive scalar isotropic turbulence was discussed by Donzis, Sreenivasan & Yeung (2010).…”
Section: Introductionmentioning
confidence: 99%